The essential role of Aesthetic Medicine in facial paralysis: combination of techniques - Moutinho-Guilherme, Ricardo; Juan, López (Aesthetic Medicine, 2024)
The face is the first point of contact in communication interactions; it reveals the person’s feelings and emotions. Injuries caused to the facial nerve, which is responsible for the innervation of the facial mimic muscles, can have important physical, psychological and even social repercussions. Bell’s palsy or idiopathic peripheral facial paralysis is the most common cause and is characterized by unilateral paralysis of the muscles, producing a clear pattern of asymmetric facial expressions. Patients with facial paralysis have common features: the paralyzed side has few wrinkles, the nasolabial fold is less evident, and drooping of the labial commissure and eyebrow may occur; the contralateral side responds with a muscle hyperkinetic reaction. The treatment of facial paralysis aims to recover symmetry in both static and dynamic states, with the combination of surgical and aesthetic methods playing an essential role in the treatment of this pathology. In the search for local symmetry, Aesthetic Medicine plays an important part, by using different methods, such as botulinum toxin injections or hyaluronic acid fillers application. In this sense, this article aims to present a case of a woman affected by facial paralysis, in whom Aesthetic Medicine played an essential role in self-esteem and functional recovery. With clinical improvement, softening asymmetries and reducing hyperkinetic muscle activity proved to have an essential impact in this patient’s facial asymmetry, promoting a considerable enhancement in quality of life and social well-being.